MULTICAGE CAD-4: Psychometric characteristics for the screening of addictive behaviors - Rodríguez Monje, Mª Teresa; Pedrero Pérez, Eduardo J.; Rodríguez Monje, Mª Teresa; Rodríguez Alonso, Elías; Rodríguez Alonso, Elías; Fernández Girón, Mercedes; Fernández Girón, Mercedes; Mateo Madurga, Alicia; Mateo Madurga, Alicia; Arana Cañedo-Argüelles, Celina; Arana Cañedo-Argüelles, Celina; Pastor Ramos, Victoria; et al. (Anales de Psicología / Annals of Psychology, 2018)
Addictive behaviors are not limited to drugs use, but also include certain daily behaviors that can cause gratification. Their progression to more severe pathological patterns entails grave consequences for the individual, including multiple psychopathological manifestations. The early detection of this type of behavior is of concern to primary health care. Therefore, in order to detect risk at early stages, reliable and valid tools for daily practice are essential. The MULTICAGE CAD-4 questionnaire is a screening tool for simultaneously detecting addictive behaviors. This study includes a new scale for the detection of smartphone abuse. The objective is to evaluate the adequacy of its psychometric properties. A sample of 2,074 subjects that were recruited from primary care centers ofMadrid(Spain) completed the MULTICAGE CAD-4 questionnaire. A confirmatory factor analysis, using unweighted least squares method, was performed. The test showed good internal consistency both at item and scale levels. The questionnaire structure was consistent with theoretical expectations. The MULTICAGE CAD-4, including the new smartphone scale, is a robust, reliable tool with a valid structure for assessing the presence of dysfunctional or potentially addictive behaviors, and especially useful in primary health care services.